Myoglobinuria and Skeletal Muscle Phosphorylase Deficiency: Report of a Case of McArdle's Disease - Nixon, J. C. (1966)
Investigation of a patient complaining of exercise-induced dark urine, pain, stiffness and tenderness of skeletal muscle revealed findings characteristic of McArdle's disease. The dark urine was attributable to the excretion of myoglobin, and an ischemic exercise test failed to demonstrate the usual rise and fall in blood lactate and pyruvate. Enzyme assays of skeletal muscle showed an absence of phosphorylase, a slight increase in phosphorylase b kinase and a slight decrease in phosphoglucomutase. Chemical and histochemical analyses demonstrated an increase in the skeletal muscle glycogen content and an enlargement of the muscle cells. No abnormality of liver glycogen metabolism was found. In the absence of specific therapy, an effective and practical form of treatment is reduction of exercise below the threshold of symptoms.